2017
DOI: 10.1016/j.jsxm.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Analysis of Four Missense Mutations in the HSD17B3 Gene Associated with 46, XY Disorders of Sex Development in Egyptian Patients

Abstract: Background Mutations in the HSD17B3 gene are associated with a 46,XY disorder of sexual development (46,XY DSD) as a result of low testosterone production during embryogenesis. Aim To elucidate the molecular basis of the disorder by chemically analyzing four missense mutations in HSD17B3 (T54A, M164T, L194P, G289S) from Egyptian patients with 46,XY DSD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In addition to DSD, it was reported that G289S is associated with the risks of prostate cancer and hypospadias [33,45]. However, consistent with our results, the enzymatic activity of these mutant proteins associated with this mutation was reported to be similar to that of wild-type protein in multiple previous studies [7,46,47]. Furthermore, the amino acid residue at this position is serine in almost all mammalian species except for primates (Figure 1A), although no studies have shown the associated susceptibility to prostate cancer and hypospadias in particular animal species.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to DSD, it was reported that G289S is associated with the risks of prostate cancer and hypospadias [33,45]. However, consistent with our results, the enzymatic activity of these mutant proteins associated with this mutation was reported to be similar to that of wild-type protein in multiple previous studies [7,46,47]. Furthermore, the amino acid residue at this position is serine in almost all mammalian species except for primates (Figure 1A), although no studies have shown the associated susceptibility to prostate cancer and hypospadias in particular animal species.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, we propose a similar trend of androgen profile in the intrauterine period with higher T and T/A leading to frequent atypical genitalia and hence, initial male sex of rearing. The residual 17βHSD3 enzyme activity can explain the higher serum T and T/A in these patients 17 . However, many patients harbouring molecular variants causing severe deficiency of the 17βHSD3 enzyme also had higher T/A, suggesting a possible role of other isoenzymes like 17βHSD5.…”
Section: Discussionmentioning
confidence: 96%
“…The residual 17βHSD3 enzyme activity can explain the higher serum T and T/A in these patients. 17 However, many patients harbouring molecular variants causing severe deficiency of the 17βHSD3 enzyme also had higher T/A, suggesting a possible role of other isoenzymes like 17βHSD5. Notably, the initial male sex of rearing was significantly more frequent in Asians but less frequent in Europeans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This novel alteration has not been reported earlier in the literature for the HSD17B3 gene. So far, more than 30 different mutations in this gene have been identified, including insertion, exonic deletion, missense, and nonsense mutations (6) with the p. Arg80Gln alteration being the most common one in the Arab population (2). In the Turkish population, c655-1;G-A, p.Ala188Val, and c.777-783del_GATAACC mutations have previously been identified (11).…”
Section: Discussionmentioning
confidence: 99%
“…Affected individuals have female external genitalia with male normal wolffian ducts at birth (4). The incidence of this disorder is estimated at 1 T in 147,000 newborns (5) and is higher in the Arab population of Gaza, and its prevalence is approximately 1 in every 200 to 300 people, which is due to the high rate of consanguineous marriages (6). Pathogenic mutations in the HSD17B3 gene (MIM# 264300) are associated with the impaired sexual development of the 46, XY fetuses.…”
Section: Introductionmentioning
confidence: 99%